Heart frequency and lactate concentration in blood with karate athletes, during the simulated and official competitions - Kostovski, Z.; Zaborski, B.; Bratovcic, V. (Sport Science - International Scientific Journal of Kinesiology, 2017)
A research has been conducted on a sample of 29 representatives - male extracted from the Karate population, a potential representative from the adult categories of younger seniors (U21) and seniors of the Republic of Macedonia. The main purpose of the research is to determine the changes that occur in cardiac frequency and blood lactate levels in senior karate athletes. For the realization of the research and monitoring of the heart rate in this research, the latest technology of the Polar Team App was used, which was specially designed for the use and monitoring of exercise processes in indoor sports (hall). A portable Scout + Lactate analyser device was used to determine the amount of lactates in the blood. During the simulated matches, the obtained mean values of the heart rate (134.69 HRavg to 147.41 HRavg) are lower than those obtained during the official matches with a value of (175.77 HRavg). As for the height of the lactates, high variability in response to lactates in the blood was determined, showing a different anaerobic glycolytic contribution. To determine the differences between the two measurements, a T-test for small dependent samples was applied.